Strategies Towards Third Party Logistics Provider in Malaysia: A Case Study on Konsortium Logistics Berhad - Lai, Shane Reza (2010)
This paper attempts to explore the strategies for a container haulier, third party logistic player in Malaysia. This industry has gone through many changes over the past decade as it has transformed from an oligopolistic to perfect competition. The paper is specifically targeted towards a case study on a pioneer firm and one of the largest haulier in the industry, Konsortium Logistics Berhad. It explores the findings of Konsortium’s haulage division and comes up with some financial strategies relating to Activity Based Management and the Balanced Scorecard methods along with some Change Management techniques that can be implemented to improve the business operations and culture of the organization. These methods are not only meant to reduce cost but also change the image of the organization. Literature review on improving the third party logistics provider is stated and basic research methodologies are applied along with the findings to obtain recommendations and strategies for the company to sustain in this industry.